Information services today an introduction - Hirsh, Sandra 1965- (Rowman & Littlefield, 2022)
"This book demonstrates the ever-changing landscape of information services today and the need to re-evaluate curriculum, competency training, professional development, and lifelong learning in order to stay abreast of current trends and issues, and more significantly, remain competent to address the changing user needs of the information community"--